The Role of Cybersecurity Knowledge and Awareness in Cybersecurity Intention and Behavior in the United States - Lee, Claire Seungeun (Crime & delinquency, 2024)
Despite the rapid escalation of cybercrimes in modern society, few viable cybersecurity and cybercrime prevention programs exist. Consequently, this research considers cybersecurity as a key element for mitigating the potential risk and incidents of cybercrime. The study aims to understand the role of individuals’ cybersecurity knowledge and awareness in shaping their cybersecurity intention and behavior in the United States. The results reveal that information and communications technology variables, education, income, and gender are contributing predictors of a level of cybersecurity knowledge. The effects of information and communications technology variables varied across gender for both correct and uncertain responses. The findings highlight the importance of a comprehensive understanding of both technical and human/individual factors for cybersecurity knowledge and education.